G278(P) What is the estimated prevalence of autism in a rural population of Nepali children?. (27th April 2016) - Heys, M; Medeiros, E; Tumbahangphe, KM; Gibbons, F; Wickenden, M; Shrestha, M; Costello, A; Manandhar, D; Pellicano, L
Abstract : Background: Autism is a global phenomenon. Epidemiological studies estimate that 1–2% of children worldwide lie on the autism spectrum, 1 with approximately 52 million individuals with autism across the globe. These estimates are largely driven, however, by prevalence estimates from high-income countries (HIC). Virtually no data exist, however, on the prevalence of autism in low-income countries (LIC) and none in a LIC rural setting. Aims: Develop a Nepali language version of a screening tool for autism Estimate prevalence of autism in a rural population of 10–13 year-old Nepali children Methods: The Autism Quotient-10 (AQ-10) is a well-validated brief questionnaire of the 10 statements most strongly predictive of a diagnosis of autism in a UK population of children (sensitivity: 95%; specificity: 97%). 2 We translated the AQ-10 – adolescent version in discussion with UK and Nepali paediatricians and clinical psychologists. The translated version was further developed and tested for acceptability in 3 focus groups of parents (n = 25). It was then piloted as a questionnaire with 136 families, following which minor edits were made only and additional fieldworker training provided. We conducted face-to-face interviews with 3984 parents from a cohort of 10–13 year-old children recruited from a 10-year follow-up study of a trial of women's participatory groups. 3 These families live in Makwanpur, a rural district of Nepal. Results: Eleven out of 3984 children scored greater than 6 out of 10, indicative of autistic symptomatology. If the AQ-10 screening tool is as sensitive and specific in the Nepali population as it is in the UK, this would give an estimated true prevalence of 3 in 1000 (95% confidence interval 2 to 5 in 1000). 4 Conclusion: This is the first study to estimate prevalence of autism in a rural LIC setting. Prevalence estimates were lower than those in HIC. Future research is required to validate this tool through in-depth comprehensive assessments of high-scoring children. This preliminary estimate, combined with complementary research showing the lack of awareness of autism by Nepali professionals and parents, stresses the need to develop services to support families and children with atypical development in rural LIC settings.